Application Of PAIKEM GEMBROT Learning Model to Improve Fifth Graders’ Science Learning Motivation - Lestari, Widya Indah Susi; Hermita, Neni; Kurniaman, Otang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This study aims to determine students' learning motivation on the use of the PAIKEM GEMBROT model. This research conducted at public elementary school located in Pekanbaru. This study uses a quantitative approach due to the data collected is in the form of numbers which are then analyzed by statistics. By the problem under the study, this research is an experimental research using the pre experiment type of one group pretest-posttest design. The subjects in this study were fifth graders’ students from a Public Elementary School with a total of 30 students. The instrument in this study used a questionnaire. The results showed that the pretest score obtained a score of 35% than expected. This means that students' learning motivation in science is still very low. After the use of the PAIKEM GEMBROT model, the Posttest was conducted with the score obtained 69.41% than expected. This means that students' learning motivation in science is high. Based on the N Gain analysis, the influence of the PAIKEM GEMBROT model on student learning motivation was 52.94% with the medium category.